Protein Phosphatase 2A: More Than a Passenger in the Regulation of Epithelial Cell–Cell Junctions - Schuhmacher, Diana; Sontag, Jean-Marie; Sontag, Estelle (Frontiers in Cell and Developmental Biology, 2019)
Cell-cell adhesion plays a key role in the maintenance of the epithelial barrier and apicobasal cell polarity, which is crucial for homeostasis. Disruption of cell-cell adhesion is a hallmark of numerous pathological conditions, including invasive carcinomas. Adhesion between apposing cells is primarily regulated by three types of junctional structures: Desmosomes, adherens junctions, and tight junctions. Cell junctional structures are highly regulated multiprotein complexes that also serve as signaling platforms to control epithelial cell function. The biogenesis, integrity, and stability of cell junctions is controlled by complex regulatory interactions with cytoskeletal and polarity proteins, as well as modulation of key component proteins by phosphorylation/dephosphorylation processes. Not surprisingly, many essential signaling molecules, including protein Ser/Thr phosphatase 2A (PP2A) are associated with intercellular junctions. Here, we examine how major PP2A enzymes regulate epithelial cell-cell junctions, either directly by associating with and dephosphorylating component proteins, or indirectly by affecting signaling pathways that control junctional integrity and cytoskeletal dynamics. PP2A deregulation has severe consequences on the stability and functionality of these structures, and disruption of cell-cell adhesion and cell polarity likely contribute to the link between PP2A dysfunction and human carcinomas.